Governing those who live an “ignoble existence”: Frontier administration and the impact of native tribesmen along the Tang dynasty’s southwestern frontier, 618-907 A.D. - Stutzman, Cameron R. (Kansas State University, 2018)
As the Tang dynasty rose to power and expanded into the present-day provinces of Sichuan and Yunnan, an endemic problem of troublesome frontier officials appeared along the border prefectures. Modern scholars have largely embraced Chinese historical scholarship believing that the lawlessness and remoteness of these southwestern border regions bred immoral, corrupt, and violent officials. Such observations fail to understand the southwest as a dynamic region that exposed assigned border officials to manage areas containing hardship, war, and unreceptive aboriginal tribes. Instead, the ability to act as an “effective” official, that is to bring peace domestically and abroad, reflected less the personal characteristics of an official and rather the relationship these officials had with the local native tribes. Evidence suggests that Tang, Tibetan, and Nanzhao hegemony along the southwestern border regions fluctuated according to which state currently possessed the allegiance of the native tribesmen. As protectors and maintainers of the roads, states possessing the allegiance of the local peoples possessed a tactical advantage, resulting in ongoing attacks and raids into the border prefectures by China’s rivals. Local officials without the allegiance of the locals and encountering attacks succumbed to improper behaviors to maintain control.
Keywords: Tang dynasty; Southwestern border; Frontier relations; Medieval China; Jiannan; Chinese administration